БАЗОВІ СКЛАДОВІ ТЕОРЕТИКО-МЕТОДИЧНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ УКРАЇНСЬКОЇ МОВИ - Рускуліс, Лілія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті проаналізовано базові складові теоретико-методичної підготовки майбутнього вчителя української мови: засвоєння лінгвістичних засад та психолого-педагогічних чинників; розуміння необхідності урахування лінгводидактичного аспекту під час викладання мови (підходи, аспекти, закономірності навчання мови); добір традиційних та інноваційних методів навчання, форм навчання; готовність до використання інформаційних технологій, комп’ютеризованих систем та формування культури мовлення майбутнього вчителя-словесника. В статье проанализированы базовые составляющие теоретико-методической подготовки будущего учителя украинского языка: усвоение лингвистических основ и психолого-педагогических факторов; понимание необходимости учета лингводидактичного аспекта во время преподавания языка (подходы, аспекты, закономерности обучения языку); отбор традиционных и инновационных методов обучения, форм обучения; готовность будущего учителя к использованию информационных технологий, компьютеризированных систем и формирование культуры речи. The article deals the basic components of theoretical and methodological training of future teachers of Ukrainian language: the mastering linguistic, psychological and educational factors; the understanding of the need to incorporate linguodidactic aspects in teaching languages; the selection of traditional and innovative methods of teaching, of learning forms; the readiness of the future expert to use information technology, computer systems and a culture of speech of future teachers-language and literature. The author analyzes the information description of disciplines of professional competencies, describes the basic aspects, patterns and approaches to teaching, principles, specific methods and techniques in studies features the introduction of information and communication technologies in the learning process and the problems of speech of student-philologist (precision, relevance, consistency, regulatory, wealth etc.). The theoretical material is presented in a synthesis scheme.